The ethnography of landscape : GIS and remote sensing in the study of forest change in West African Guinea Savanna. - Nyerges, A. Endre (American Antropological Association, 2000)
In this paper we explore the application of Amazonian forest change models to the Guinea savanna environment of western Africa. In particular, we examine recent research documenting the growth of peri-village forest islands in the area of Kissidougou, Guinea, which purports to challenge the pervasive view of Guinea savanna deforestation brought about by human activity. As a more systematic approach to the analysis of human/environmental interactions, we propose an "ethnography of landscape," in which the findings of detailed, local ethnographic and ecological case studies are combined with remotely sensed information on what the wider region looks like as it changes over time. In pursuing this research, we employ aerial photography and Geographic Information Systems (GIS) techniques to examine our study area of Kilimi in northwestern Sierra Leone. We show that a Kissidougou-type model of peri-village forest island growth is not applicable to this region, where other environmental change processes are underway. In future work, we propose to employ Landsat satellite image archives to examine, monitor, and compare processes of ecological change throughout the Guinea savanna.